2008
DOI: 10.1007/bf03161210
|View full text |Cite
|
Sign up to set email alerts
|

Lamotrigine-associated reversible severe hepatitis: A case report

Abstract: A 43-year-old woman with a history of depression, which was being treated with oxcarbazepine twice a day (300 mg/morning and 450 mg/evening), was started on lamotrigine 2 weeks prior to her presentation, with the dose increased to 50 mg/day just prior to admission.Two weeks after starting the lamotrigine, she developed nausea and a generalized pruritic macular rash. She sought treatment in ABSTRACTIntroduction: Anticonvulsant hypersensitivity syndrome is a severe idiosyncratic reaction to antiepileptic drugs.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…Severe rashes due to lamotrigine occurr almost regularly within the fi rst 6 -8 weeks of exposure, rarely after 12 weeks and almost exclusively later (30). Several reports of lamotrigine-induced DRESS syndrome have been reported in the literature (12,27,28,29,(31)(32)(33)(34). Th e second psychoactive drug our patient was taking in combination with lamotrigine was an antipsychotic -olanzapine, an oxazepine that is prescribed to patients with schizophrenia or recurrent bipolar disorder.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Severe rashes due to lamotrigine occurr almost regularly within the fi rst 6 -8 weeks of exposure, rarely after 12 weeks and almost exclusively later (30). Several reports of lamotrigine-induced DRESS syndrome have been reported in the literature (12,27,28,29,(31)(32)(33)(34). Th e second psychoactive drug our patient was taking in combination with lamotrigine was an antipsychotic -olanzapine, an oxazepine that is prescribed to patients with schizophrenia or recurrent bipolar disorder.…”
Section: Discussionmentioning
confidence: 91%
“…Lamotrigine [6-(2,3-dichlorophenyl)-1,2,4-triazine-3,5-diamine] is an antiepileptic drug, used in the management of a broad range of seizures in adults and children which is not an aromatic antiepileptic, thus being structurally and pharmacologically unrelated to other antiepileptic medications e.g. carbamazepine (28,29). Lamotrigine has been repoted in association with severe skin rash, multiorgan failure, DRESS syndrome, acute hepatic failure, and disseminated intravascular coagulation.…”
Section: Discussionmentioning
confidence: 99%
“…Clarkson and Choonara [16] and Su-Yin et al [17] once reported that VPA/LTG can cause liver injury to different degrees. Hepatic injuries associated with these AEDs could be classified into two subtypes: the common type and the fulminant liver failure type.…”
Section: Discussionmentioning
confidence: 99%
“…Clarkson et al [5,6] once reported that VPA/LTG can cause liver damage to various degrees, and hepatic injuries associated with these drugs can be classified to two subtypes: common type and fulminant liver failure. The former manifests temporary and reversible elevation of bilirubin and liver enzyme values, which is usually dose-dependent and the abnormality can return to normal shortly after the drug is withdrawn [24]; the latter is life-threatening and infrequent, occurring generally within 2-8 weeks (LTG) or 3 months (VPA) after initiating the use of LTG/VPA [25,26].…”
Section: Discussionmentioning
confidence: 99%
“…It has been known that certain antiepileptic drugs (AEDs) such as valproic acid (VPA) and lamotrigine (LTG) would give rise to the hepatic injury, ranging from mild and reversible abnormality of liver function tests to serious hepatotoxicity [5,6]. However, Levetiracetam (LEV), which is metabolized by enzymatic hydrolysis of the acetamide group in blood rather than liver cytochrome P450 enzymes, and excreted by the urinary system [7,8], has a minor effect on liver function.…”
Section: Introductionmentioning
confidence: 99%